Needle Syringe Program-Based Primary HealthCare Centers - M. Mofizul Islam MSc (SAGE Publishing, 2010)
Needle syringe programs (NSPs) are now on a strong platform mainly because of their crucial role in controlling/containing blood-borne virus infections. In many parts of the world, NSPs are gradually augmenting their role as a primary health care centers. Health care from NSPs are found to be better accessible by injecting drug users (IDUs). However, these outlets are becoming a separate source of health care for IDUs-mainly because (i) nondrug users very rarely access these and (ii) IDUs do not access other sources of primary care readily. Moreover, offering health care from NSPs is also relatively cost-intensive, therefore, has some disadvantages. The aim of this commentary is to examine and discuss the advantages and disadvantages of NSP-based primary health care outlets. The benefits NSPs can accrue through offering health care services are immense, as an NSP is a critical junction for service providers to offer health care services to IDUs, who traditionally have been hard to reach by conventional health care. Despite some disadvantages, NSP-based health care is very valuable for IDUs until they are duly taken care by the conventional health care centers.